2022
DOI: 10.1177/15563316221090508
|View full text |Cite
|
Sign up to set email alerts
|

Nonagenarians and Octogenarians Undergoing THA and TKA: A 10-Year Age Difference Increases Rates of In-Hospital Complications But Does Not Affect 90-Day Outcomes

Abstract: Background: The population of nonagenarians undergoing total joint arthroplasty (TJA) of the hip or knee is expected to increase, but this population may be reluctant to consider elective surgery because of their advanced age. Purpose: We sought to compare TJA outcomes between nonagenarians and octogenarians with an exact 10-year age difference. Methods: We performed a retrospective chart review, including 129 nonagenarians who underwent primary unilateral TJA for osteoarthritis in a 4-year period at a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…2,10 The longer hospital stay is attributed to many factors, not just the higher perioperative complications. 5,9,12 Our data confirmed previously reported data on the higher cost of care (COC) in this patient population. Fang et al, reported that nonagenarians had significantly higher implant and total-in-hospital costs for total joint arthroplasty in comparison to octogenarians.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…2,10 The longer hospital stay is attributed to many factors, not just the higher perioperative complications. 5,9,12 Our data confirmed previously reported data on the higher cost of care (COC) in this patient population. Fang et al, reported that nonagenarians had significantly higher implant and total-in-hospital costs for total joint arthroplasty in comparison to octogenarians.…”
Section: Discussionsupporting
confidence: 90%
“…2 Nonagenarians are at a greater risk of perioperative complications. 9 Previous studies have demonstrated a higher risk of complications following THAs. 2,5,12,13 The nonagenarians are often with medical co-morbidities, some of which may not be modifiable before or after THAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies on joint replacement surgery among older patients compared to younger patients have reported increased risk of multiple medical complications, longer hospital stays, readmission, and mortality. 4 , 9 , 10 , 11 , 19 , 21 However, understanding how each increased decade of life affects adverse outcomes has not been explored. Further investigation to stratify postoperative outcomes within older age groups may help to better understand as to which adverse outcomes certain patient groups are at higher risk.…”
mentioning
confidence: 99%